Accuracy of tidal breathing measurement of floright compared to an ultrasonic flowmeter in infants. Issue 4 (20th February 2014) - Petrus, Nicole C.M.; Thamrin, Cindy; Fuchs, Oliver; Frey, Urs
Summary: Introduction: Monitoring breathing pattern is especially relevant in infants with lung disease. Recently, a vest‐based inductive plethysmograph system (FloRight®) has been developed for tidal breathing measurement in infants. We investigated the accuracy of tidal breathing flow volume loop (TBFVL) measurements in healthy term‐born infants and infants with lung disease by the vest‐based system in comparison to an ultrasonic flowmeter (USFM) with a face mask. We also investigated whether the system discriminates between healthy infants and those with lung disease. Methods: Floright® measures changes in thoracoabdominal volume during tidal breathing through magnetic field changes generated by current‐carrying conductor coils in an elastic vest. Simultaneous TBFVL measurements by the vest‐based system and the USFM were performed at 44 weeks corrected postmenstrual age during quiet unsedated sleep. TBFVL parameters derived by both techniques and within both groups were compared. Results: We included 19 healthy infants and 18 infants with lung disease. Tidal volume per body weight derived by the vest‐based system was significantly lower with a mean difference (95% CI) of −1.33 ml/kg (−1.73; −0.92), P < 0.001. Respiratory rate and ratio of time to peak tidal expiratory flow over total expiratory time (tPTEF/tE) did not differ between the two techniques. Both systems were able to discriminate between healthy infants and those with lung disease using tPTEF/tE. Conclusion: FloRight® accurately measures time indices and may discriminate between healthy infants and those with lung disease, but demonstrates differences in tidal volume measurements. It may be better suited to monitor breathing pattern than for TBFVL measurements.Pediatr Pulmonol. 2015; 50:380–388. © 2014 Wiley Periodicals, Inc.